(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The process of increasing the speed of the internet in the present time is of great interest to researchers. In this paper we reviewed the Light Fidelity (Li-Fi) technology, which is the future of communications that will provide solutions to the problems of bottlenecks. This technology has the ability to transfer data rate at very high speed of up to 100 times faster than Wi-Fi technology The focus of this paper is on the definition of Li-Fi and the applications, benefits, disadvantages of Li-Fi technology and the future uses of this technology as compared to the existing ones such as Wi-Fi technology, where the abundance of technology for Wi-Fi offers a larger package ,a better work efficiency and a greater security of data transfer technologies Currently exist.